Pengaruh Kecepatan Angin pada Karakteristik Performansi Konduktor SUTET - Suprihadi Prasetyono (Fakultas Teknik, Universitas Jember, 2015)
AbstractWind speed changes at SUTET conductor besides having coolingeffects it also improves the transmission line capacities and will giveinfluence to conductor performances. This research aimed to knowthe influence of the wind speed to performance conductorcharacteristics such as temperature, tension, length, sag andcurrent carrying capacity of conductor. As simulation model, anextra high voltage transmission line 500kV Paiton – Kediri span no10 is used. Temperature of Conductor is calculated based on hotbalanceequation, whereas Catenary method and Rulling spanmethod used to determine sag conductor and length. The result ofcalculation shows, that the wind speed can be used to coolconductor with the range from 1 - 3 degree of celcius each for everyincrease of wind speed for 0,5 m / s. While conductor mechanicalcharacteristics such as tension, length, and sag does not having anysignificant changes.Keyword : Mechanical performance, Transmission line, Conductor.